Jenkins administrator's guide : install, manage and scale a CI/CD build and release system to accelerate your product lifecycle /: install, manage and scale a CI/CD build and release system to accelerate your product lifecycle. (2021) - Park, Calvin Sangbin; Adithya, Lalit; Gleske, Samuel
No abstract available